ANALISIS PERBANDINGAN KEPUASAN OBAT TRADISIONAL DAN OBAT MODERN DALAM SWAMEDIKASI PADA PASIEN BATUK DAN FLU - Adiputri, Nadya; Putri, Elgiva Leana; Habibah, Nasywa Aulia Salsabil (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2024)
Self-medication is the act of using medicine without diagnosis and supervision from healthcare professionals, which is commonly practiced by the public to address minor complaints such as coughs and colds. Although it is practical, improper self-medication has the potential to cause various health risks. This study aims to identify differences in levels of satisfaction and perceptions of the effectiveness of using traditional and modern medicines in self-medicating coughs and colds in the community. This study employs a quantitative method with a cross-sectional design. Data collection was carried out through an online questionnaire using Google Forms among respondents who had previously self-medicated for coughs and colds. The research instruments included demographic data as well as satisfaction assessments based on a Likert scale regarding the effectiveness, safety, and convenience of medication use. The data were analyzed descriptively and comparatively to observe differences in satisfaction levels between users of traditional and modern medicines